The Racial Implications of Tort Reform - Joanne Doroshow; Amy Widman (Washington University Journal of Law & Policy, 2007)
This Article examines some of the ways racial issues have been deliberately concealed by the rhetoric of the “tort reform” movement, and how tort reform proposals will have a disparate impact on racial and ethnic minorities. In particular, it analyzes some of the pillars of the tort reform movement: attacks on the medical malpractice system, limits on non-economic damages, class actions, and political attacks against the jury system. It also examines specific cases involving hate crimes and environmental justice, illustrating the importance of the tort system in furthering racial justice.
Keywords: Sociological jurisprudence; Tort reform; Race discrimination; Critical race theory; Health care services accessibility; Medical malpractice; United States